O autoritarismo no processo penal brasileiro : uma análise da categoria “livre convencimento” no Supremo Tribunal Federal - Leonel, Juliano de Oliveira (2022)
The present work has the purpose of analyzing the authoritarian structure of the Brazilian criminal procedure, which, even in the face of the political rupture operated with the Federal Constitution of 1988, with the establishment of the so-called Democratic State of Law, still remains "alive", in a true “crisis of legal sources”. This is because the Criminal Procedure Code, with a clear fascist bias, has managed to "cross" the various Brazilian constitutional orders, since its entry into force in 1941, in order to show that democracy is not capable of resisting and preventing the existence authoritarianism at its core. Furthermore, the maintenance of authoritarianism in criminal proceedings can be largely credited to the genetic omission of the Federal Supreme Court in confronting the authoritarian category – free conviction, based on the legacy of legal technicality in Brazilian “post-accusatory” thinking, as well as as for the non-reception of the linguistic turn and consequent maintenance of the dualistic subject-object scheme in the interpretation, either because the judges are still based on classical metaphysics or on the philosophy of consciousness. In this way, admitting the polysemy of the term authoritarianism, in addition to the insufficiency of sociopolitical concepts, the expression "in" and "for" the criminal process will be substantive, revealing, within this scenario, the use of the criminal process as a criminal policy in the service of ideology of social defense to the detriment of the protection of individual rights and guarantees provided for in the Federal Constitution. Furthermore, free conviction, as an authoritarian category and a rhetorical statement, plays an important role in maintaining decisions that are incongruous with a theory of law committed to the search for an adequate response to the Constitution, from a paradigm of philosophical hermeneutics. Therefore, based on a “genealogy” of free conviction in the decisions of the Federal Supreme Court, the contribution of the Supreme Court in maintaining authoritarianism in criminal proceedings will be demonstrated, in disagreement with the provisions of the Federal Constitution of 1988.